Preparation of Hydrochar from Longan Peel: A Promising Adsorbent for Cationic Dye Removal in Aqueous Solutions - Wijaya, Alfan; Ardiansyah, Redo; Augustiara, Elsha; Fajri, Shahibul (Indonesian Journal of Material Research, 2024)
This study successfully prepared longan peel hydrochar via hydrothermal carbonization, characterized and evaluated for its adsorption capacity of cationic dyes malachite green (MG) and rhodamine B (RhB) in aqueous solution. Material characterization through XRD analysis revealed diffraction peaks indicative of carbonaceous content, supported by FTIR results showing OH, C-O, and C-O-C functional groups. The BET analysis showed a surface area of 18.712 m2/g, and SEM images displayed a heterogeneous, irregular surface morphology with spherical particles. The longan peel hydrochar exhibited adsorption capacities of 117.647 mg/g for MG and 50.505 mg/g for RhB, with MG showing greater selectivity, as demonstrated through dye mixture adsorption tests. The adsorption process was spontaneous, endothermic, and conformed to the pseudo-second-order kinetic model. Adsorption of MG followed the Freundlich isotherm, while RhB adsorption conformed to the Langmuir isotherm. Additionally, the hydrochar exhibited reusability for up to two adsorption cycles, indicating its potential as an effective adsorbent for cationic dye removal from aqueous solutions.